2010
DOI: 10.1111/j.1467-9396.2010.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Investment Liberalization and Cross-Border Acquisitions: The Effect of Partial Foreign Ownership

Abstract: This paper investigates the optimal strategy for a multinational to conduct FDI. We find that the incentives to use acquisition rather than greenfield investment change significantly if the multinational is allowed to have already an ownership interest in the target local firm before the market is fully liberalized. Interestingly, when investment costs are sufficiently high, the multinational prefers not entering the market at all with partial ownership in place, whereas a cross-border takeover would be the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The seminal paper in this area is Brouthers (2002) and has been followed by numerous other studies. Many studies in the IB literature go beyond the traditional greenfield versus M&A distinction and include entry modes such as JVs and partial acquisitions, which provide a much more disaggregated way of looking at the participation of firms in foreign markets (Fatica 2010). In this paper, foreign market participation is disaggregated into five different categories: wholly owned subsidiaries, JVs, acquisitions, new plants and representative offices (Wooster, Blanco, and Charles Sawyer 2014).…”
Section: The Determinants Of Fdi and The Case Of Latin Americamentioning
confidence: 99%
“…The seminal paper in this area is Brouthers (2002) and has been followed by numerous other studies. Many studies in the IB literature go beyond the traditional greenfield versus M&A distinction and include entry modes such as JVs and partial acquisitions, which provide a much more disaggregated way of looking at the participation of firms in foreign markets (Fatica 2010). In this paper, foreign market participation is disaggregated into five different categories: wholly owned subsidiaries, JVs, acquisitions, new plants and representative offices (Wooster, Blanco, and Charles Sawyer 2014).…”
Section: The Determinants Of Fdi and The Case Of Latin Americamentioning
confidence: 99%
“…Results are that, contrary to mergers, vertical PO align both firms' interests and do not lead to a potentially anticompetitive foreclosure. Fatica () studies the effects of POs prior to foreign direct investments. It is shown that toeholds can facilitate full acquisition over a green field investment though the result depends on the value of investment costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results are that, contrary to mergers, vertical PO align both firms' interests and do not lead to a potentially anticompetitive foreclosure. Fatica (2010) (Besen, Murdoch, OBrien, Salop, & Woodbury, 1999), "Keiretsu" in Japan (Brown & Fung, 2009), "Deutschland AG" in Germany (Lantenois, 2011),…”
Section: Mergers and Pomentioning
confidence: 99%
“…In addition to the above‐mentioned papers, the choice between the two FDI strategies has been extensively investigated in various theoretical models. For example, Klimenko and Saggi () focus on products with network externalities, Nocke and Yeaple () emphasize the role of firm heterogeneity, Raff, Ryan, and Stähler () allow for joint venture to be a possible choice of entry mode, Kim () considers the impacts of regional economic integration, and Fatica () examines the choice by allowing the multinational firm to have partial ownership of the target firm in the host country. Karabay () and Qiu and Wang () both consider FDI restriction policies imposed by the government in the host country, Markusen and Stähler () look at the FDI policy in the context of an endogenous market structure, Norbäck and Persson () and Ray Chaudhuri () both focus on the profitability of cross‐border M&A, and Stepanok () analyzes the optimal entry mode in monopolistic competition industries, among many others.…”
Section: Related Literaturementioning
confidence: 99%